PEMBERDAYAAN PRAJURU LEMBAGA KEUANGAN MIKRO ADAT MELALUI PENERAPAN TEKNOLOGI INFORMASI DI DESA KESIUT KECAMATAN KERAMBITAN KABUPATEN TABANAN - Putu Krisna Adwitya Sanjaya; I Nyoman Suta Widnyana; I Putu Nuratama (UNHI Press, 2019)
Indonesia is preparing itself in the era of the industrial revolution 4.0. For this reason, businesses are expected to be able to maximize the use of information technology to the fullest, one of which is by preparing financial statements. But now there are not many microfinance institutions that use information technology to carry out the recording of their financial statements. This also happened in Kesiut village, located in Kerambitan sub-district, Tabanan Regency. The Indigenous Community microfinance institution still records finances manually and some even inconsistencies in carrying out the registration process. Of course this if not followed up immediately will pose a risk of future losses. The obstacle faced is the lack of professional quality human resources. Problem solving solutions are implemented by conducting socialization, training and assistance in preparing financial statements. The implementation method is carried out in several stages, beginning with providing an understanding of the importance of the use of information technology, followed by giving an overview of the general picture of how the industrial revolution occurred which could lead to diseruption. The next step is to carry out training in preparing financial statements based on information technology software. The final stage is assisted to help solve the problems faced in relation to the preparation of financial statements. Through the community partnership program which is manifested through the stages of outreach, training and mentoring, the Indigenous community microfinance institution in running its business is able to independently prepare financial reports and conduct evaluations of its business activities. By carrying out this activity it is also hoped that in the long run the Indigenous community microfinance institutions in the Kesiut village will further develop and of course with the development of indigenous community microfinance institutions, the economy in the area will also be stretched so that there will be an acceleration of the welfare of the village community.